Isolation, structure elucidation, and synthesis of antiplasmodial quinolones from Crinum firmifolium. Issue 15 (1st August 2017) - Presley, Christopher C.; Du, Yongle; Dalal, Seema; Merino, Emilio F.; Butler, Joshua H.; Rakotonandrasana, Stéphan; Rasamison, Vincent E.; Cassera, Maria B.; Kingston, David G.I.
Graphical abstract: Abstract: Antiplasmodial bioassay guided fractionation of a Madagascar collection of Crinum firmifolium led to the isolation of seven compounds. Five of the seven compounds were determined to be 2-alkylquinolin-4(1 H )-ones with varying side chains. Compounds1 and4 were determined to be known compounds with reported antiplasmodial activities, while5 was believed to be a new branched 2-alkylquinolin-4(1 H )-one, however, it was isolated in limited quantities and in admixture and therefore was synthesized to confirm its structure as a new antiplasmodial compound. Along with5, two other new and branched compounds6 and7 were synthesized as well. Accompanying the five quinolones were two known compounds2 and3 which are inactive against Plasmodium falciparum . The isolation, structure elucidation, total synthesis, and biological evaluation of these compounds are discussed in this article.